Estructura horizontal y potencial maderable de un bosque de colina baja en la cuenca del río Yavarí Mirim, provincia de Ramón Castilla, Loreto - Perú - Mendoza Panaifo, Dick Ralph (2018)
The study was carried out in a low hill forest in the Yavarí Mirim river basin, a tributary of the Yavarí river, which in turn is a tributary of the Amazon river. Politically it is located within the jurisdiction of the district of Yavarí, province of Ramón Castilla, Loreto region. The objective was to determine the horizontal structure and timber potential of commercial forest species. In 946.50 ha a total of 954 individuals distributed in 08 species, 08 genera and 08 botanical families are reported. Likewise, Virola sp. "cumala/cumala aguanillo" has the largest number of trees with a total of 421 (0.44 tree/ha), followed by Simarouba amara "marupa" with 144 trees (0.15 tree/ha). The species with the highest ecological value and that contain 50% of the total IVI. Virola sp. it is the most important species in the forest under study with 94.5%, followed by Cedrela odorata with 49.2% and Simarouba amara with 43.9%. Finally, "Cumala" has the highest number of trees, basal area and commercial volume in the forest under study with 0.27 trees/ha, 0.11 m2/ha and 1.46 m3/ha. It is necessary to carry out assessment studies of ecosystem goods and services that allow the forest user to decide how to take advantage of their forest resources.